ANALISIS DETERMINAN RETURN SAHAM INDUSTRI MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 - 2020 - Ifah Lathifah; Widi Budi Hariyanti (Jurnal Bisnis dan Kewirausahaan, 2021)
This research aims to examining factors that affect stock returns. The dependent variable used in this study is stock returns. Independent variables used in this study is Economic Value Added (EVA), Operating cash flow, Earnings, Operating Leverage, dan Market Value Added (MVA). The population in this research is manufacturing companies listed in Indonesia Stock Exchange 2017-2020. The sample in this study is 21 companies selected by using purposive sampling method. This study used multiple linear regression analysis as an analytical tool. The results showed that H1 Economic Value Added ( EVA ) had no significant effect on stock returns. H2 Operating Cash Flow is a significant effect on stock returns. H3 Earnings significant effect on stock returns. H4 Operating Leverage no significant effect on stock returns. H5 Market Value Added ( MVA ) had no significant effect on stock returns.